2017
DOI: 10.1017/s1431927617001921
|View full text |Cite
|
Sign up to set email alerts
|

Eye Gaze Pattern Analysis of Whole Slide Image Viewing Behavior in PathEdEx Platform

Abstract: Visual interpretation of histopathological slides is a complex process that may lead to diagnostic pitfalls. We have started a study to quantify and analyze pathologist's eye gaze patterns while viewing whole slide images (WSI) of specimens on computer monitor in order to explore and uncover diagnostic heuristics. As part of our ongoing research, we are developing a digital pathology integrative platform (DPIP) to provide a training and research resource that includes an online case-based training site, a coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Both studies concluded that the gaze of expert/fully-trained pathologists converged much more quickly towards diagnostically relevant ROIs than junior or trainee pathologists. PathEdEx, an online tool that records and automatically groups the gaze patterns of pathologists was introduced in [17]. The resulting clusters, along with clinical notes added by expert pathologists, were then employed for training of pathology students and trainees.…”
Section: Related Workmentioning
confidence: 99%
“…Both studies concluded that the gaze of expert/fully-trained pathologists converged much more quickly towards diagnostically relevant ROIs than junior or trainee pathologists. PathEdEx, an online tool that records and automatically groups the gaze patterns of pathologists was introduced in [17]. The resulting clusters, along with clinical notes added by expert pathologists, were then employed for training of pathology students and trainees.…”
Section: Related Workmentioning
confidence: 99%